Effect of WebQuest-based education on critical thinking and academic self-efficacy of midwifery students: Study protocol of a randomized, controlled crossover trial - Azam Mohammadi; Maryam Modarres; Zohreh Khakbazan; Akram Sadat Sadat Hoseini; Mohammad Asghari-Jafarabadi; Mehrnaz Geranmayeh (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND AND AIM: Critical thinking fills the gap between theoretical and clinical teaching and increases the power of clinical decision-making. WebQuest is an innovative, learner-centered, and effort-driven learning approach that uses computer technology to engage and motivate learners. In WebQuest, learners are compelled to use the latest information available on the web as a tool to promote higher levels of thinking. However, we did not find a study that used WebQuest to improve students' critical thinking and academic self-efficacy. The aim of this study will be to investigate the effect of WebQuest-based education on the critical thinking of midwifery students. MATERIALS AND METHODS: This superiority randomized, controlled crossover trial will be carried out among fifth-semester undergraduate midwifery students. Participants will be allocated to one of two event groups (A and B) using block randomization. In the first sequence (FS) (four weeks) of study, both groups will simultaneously attend two different education groups (WebQuest and traditional). During the FS, WebQuest will be used to teach group A participants, while group B participants will be treated as the control group (CG) and be taught using a traditional presentation. In the second sequence (SS), the interventions will be crossed over. Participants in both groups will complete the sociodemographic questionnaire, the California Critical Thinking Skills Test (CCTST), the California Critical Thinking Disposition Inventory (CCTDI), and the Academic Self-Efficacy Beliefs Questionnaire (ASEBQ) once before the first sequence of the study, during the washout period, and at the end of the second sequence of the study. The teaching satisfaction questionnaire will be completed at the end of the study. DISCUSSION: The results of this study can be used as a basis for teaching midwifery students using WebQuest as a new teaching method.